Factors that Influence Pregnant Women's Acceptance of ANC Visits at BPM Hj. Kokom Komariah, Cipondoh Tangerang - Lisnawati, Resty (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
The aim of this research is to determine the factors that influence mothers in making ANC visits at BPM Hj. Kokom Komariah, Cipondoh Tangerang. The type of research used was an analytical survey research method with a cross sectional design which began in July – August and was carried out on 50 pregnant women respondents, the variable used was a single one, data was collected using a questionnaire and analyzed using the chi square / Chi Square test. The research results showed that ANC visits based on the age of the majority of mothers who were not at risk amounted to 40 mothers, ANC visits based on the parity of the majority of mothers who did not have children and already had one child amounted to 35 mothers, ANC visits based on the education of the majority of mothers who had higher education amounted to 35 mothers, based on occupation, the majority of mothers who work are 35 mothers, based on knowledge, the majority are mothers who have good knowledge, numbering 26 mothers, and based on attitudes, the majority of mothers who have negative attitudes are 28 mothers. From the research results, it can be seen that there are 4 factors that have a relationship with ANC visits, namely Age, Education, Occupation and Attitude, while there are 2 factors that have no relationship with ANC visits, namely Parity and Knowledge.